Penataan Regulasi dan Iklim Penanaman Modal di Nusa Tenggara Timur - Yoshua Alehandro Adoe; Saryono Yohanes; Detji K. E. R. Nuban (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study discusses the regulatory arrangement and investment climate in East Nusa Tenggara Province (NTT) as a strategic effort to increase investment attractiveness. Although it has great potential in the agriculture, fisheries, and tourism sectors, investment development in NTT has not been optimal due to overlapping regulations, complex bureaucracy, and lack of efficiency in licensing services. Based on the Stufenbau theory from Hans Kelsen, synchronization between Regional Regulation Number 3 of 2025 and Law Number 25 of 2007 is needed so that there are no conflicts or legal vacancies that can hinder the certainty of doing business. In addition, local governments have implemented various strategies to improve the investment climate, such as improving basic infrastructure, simplifying bureaucracy, promoting regional potential, developing human resources, and strengthening security and order. Other efforts are also being made through the digitization of licensing services and cooperation with the private sector to expand investment networks. Thus, an integrated regulatory and policy arrangement is expected to be able to create a competitive and sustainable investment climate in the NTT region.